My husband eaudiobook A novel. - Ventura, Maud (HarperAudio, 2023)
In this suspenseful and darkly funny debut novel, a sophisticated French woman spends her life obsessing over her perfect husband—but can their marriage survive her passionate love? A Belletrist Book Club Pick An Amazon UK Best Book of the Year Winner of France's First Novel Prize Named a Best Book of the Summer by Vogue theSkimm Oprah Daily The Millions At forty years old, she has an enviable life: a successful career, stunning looks, a beautiful house in the suburbs, two healthy children, and most importantly, an ideal husband, whose wealthy background allows her to transcend her own social class. After fifteen years together, she is still besotted with him. But she's never quite sure that her passion is reciprocated. Determined to keep their relationship perfect, she meticulously prepares for every encounter they have, always taking care to make her actions seem effortless. She watches him attentively, testing him to make sure that he still loves her just as much as he did when they first met. Until one day she realizes she may have gone too far . . . "Fans of Caroline Kepnes' You or Gillian Flynn will find My Husband to be a new, satisfying, and unnerving take on the relationship-suspense genre." —Booklist (starred review)